Factors of Consumer Purchase Intentions in Purchasing EcoLink Lighting Products in Sidoarjo: A Qualitative Analysis - Ghifary, Rafly (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Light-emitting diode (LED) technology offers several advantages, including a longer lifespan, stability in light output, and higher efficiency compared to incandescent bulbs. EcoLink is a brand that provides high-quality, eco-friendly LED lighting at affordable prices, designed for consumers seeking reliable and long-lasting lighting solutions. The global LED lighting market share is expected to grow to around 70% by 2020, making evaluating this technology from various perspectives important. Garden LED lights are a more environmentally friendly and economical solution than traditional lights, with better energy and financial outcomes. EcoLink’s design is adapted to Indonesia’s living conditions and electrical system to create stable, uniform, and environmentally friendly lighting. LED lights are often used in energy-efficient products, consuming less energy and having a longer lifespan than traditional lights. EcoLink LEDs are proven to last longer and come with a 1-year warranty. Qualitative research methods, such as interviews and observation, are used to understand the experiences of EcoLink lighting users of all ages. These methods aim to uncover the underlying meaning of the data and provide rich and in-depth descriptions of complex phenomena. The data collection technique for this study involves interviews, which allow participants to express their thoughts and feelings in their own voice.